Published guidelines on COVID-19: Which to follow? - Manu Sundaram; Rohit Saxena; Marti Pons Odena; Giovanna Chidini; Mohammed Salameh; R N Ashwath Ram; Utpal Bhalala (Wolters Kluwer Medknow Publications, 2020)
The novel coronavirus 19 (COVID-19) pandemic has brought the world to a halt and humans at existential risk from an unknown enemy. In view of a high reproductive number, the number of deaths and people affected by COVID-19 has been unprecedented. At the same time, the knowledge sharing by the medical community from social media, networking, and the large number of publications has brought new challenges. To review the literature and bring out the best practice summary, we have involved physicians from the COVID-19 hotspots and societies to share their knowledge, experience, and transferable skills learned from helping their adult intensive care unit colleagues and managing pediatric COVID-19 patients. This has been particularly challenging as the goal post has been shifting very quickly and will continue to evolve while high-quality evidence is obtained.